(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article presents a comprehensive analysis of the impact of high moisture and ash content of Angren lignite coal on its calorific value and the efficiency of energy generation at thermal power plants. High levels of moisture and mineral impurities are shown to reduce the lower heating value of coal, increase fuel consumption, intensify fouling of boiler heat-exchange surfaces, and raise operational costs. Based on a review of domestic and international studies, the feasibility of improving coal quality through preliminary drying and beneficiation is scientifically substantiated. Within the framework of the study, a special fluidized-bed-based device was developed to enable the simultaneous implementation of coal drying and beneficiation processes. Experimental investigations were carried out under the operating conditions of the Angren Thermal Power Plant. The results demonstrated that the calorific value of B2-grade coal increased from 2200 to 3900 kcal/kg, accompanied by a significant reduction in specific fuel consumption and electricity generation costs. Economic efficiency calculations confirmed the high effectiveness and profitability of the proposed technology.